2017
DOI: 10.1002/lno.10625
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of dimethylsulfoniopropionate synthesis at high irradiance in natural phytoplankton communities of the Tropical Atlantic

Abstract: Predictions of the ocean-atmosphere flux of dimethyl sulfide will be improved by understanding what controls seasonal and regional variations in dimethylsulfoniopropionate (DMSP) production. To investigate the influence of high levels of irradiance including ultraviolet radiation (UVR), on DMSP synthesis rates (lDMSP) and inorganic carbon fixation (lPOC) by natural phytoplankton communities, nine experiments were carried out at different locations in the low nutrient, high light environment of the northeastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…While an intriguing hypothesis, further studies are needed to understand if different DMSP synthesis genes explain the differential regulation of DMSP by LoDPs and HiDPs and to determine the DMSP synthesis genes of other organisms not predicted to contain dysB, DYSB, or TpMMT (e.g., Trichodesmium ). Future studies incorporating direct measurements of DMSP synthesis (Stefels et al ; Archer et al ) with genomic measurements (Curson et al , ) will help decipher the physiological mechanisms behind differential LoDP and HiDP regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While an intriguing hypothesis, further studies are needed to understand if different DMSP synthesis genes explain the differential regulation of DMSP by LoDPs and HiDPs and to determine the DMSP synthesis genes of other organisms not predicted to contain dysB, DYSB, or TpMMT (e.g., Trichodesmium ). Future studies incorporating direct measurements of DMSP synthesis (Stefels et al ; Archer et al ) with genomic measurements (Curson et al , ) will help decipher the physiological mechanisms behind differential LoDP and HiDP regulation.…”
Section: Discussionmentioning
confidence: 99%
“…While an intriguing hypothesis, further studies are needed to understand if different DMSP synthesis genes explain the differential regulation of DMSP by LoDPs and HiDPs and to determine the DMSP synthesis genes of other organisms not predicted to contain dysB, DYSB, or TpMMT (e.g., Trichodesmium). Future studies incorporating direct measurements of DMSP synthesis (Stefels et al 2009;Archer et al 2017) with genomic measurements (Curson et al 2017(Curson et al , 2018 will help decipher the physiological mechanisms behind differential LoDP and HiDP regulation. While constraining the physiological mechanisms of DMSP for different phytoplankton types is critical for understanding the ecological roles of DMSP, simply differentiating between the two different types of DMSP producers was sufficient for reproducing the majority of observed spatial and temporal dynamics of in situ DMSP concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, field experiments have shown that inhibition by UV radiation is also important for algal assemblages at lower latitudes and in the open ocean. 8,79 Exposure to UV radiation also inhibits synthesis of a key organosulfur compound, dimethylsulfoniopropionate, a marine precursor to dimethyl sulfide, a gas that helps ameliorate climate warming through the generation of sulphate aerosols. 8 Laboratory studies continue to investigate how environmental factors affect the response of phytoplankton to UV radiation, and the results of these are discussed in sections 3.2-3.4.…”
Section: Inhibition Of Algal Photosynthesis and Other Processesmentioning
confidence: 99%
“…6). In the same context, a recent study using stable isotope incorporation into DMSP produced by natural phytoplanktonic communities showed that DMSP production on a diel timescale was coupled to carbon fixation rather than being stimulated at high light intensity, thus indicating that the regulation of DMSP production is not linked to photooxidative stress (Archer et al, 2018). Also considering the definition of an antioxidant as "any substance that, when present at low concentrations compared with those of an oxidizable substrate, significantly delays or prevents oxidation of that substrate" (Halliwell 1995), our observations rather support the hypothesis that DMSP and DMSO are simply damaged by ROS and do not exhibit any antioxidant property.…”
Section: Dmsp and Dmso Might Not Be Part Of The Antioxidant Networkmentioning
confidence: 99%
“…DMSO, DMS, acrylate, MSA and MSNA) (Stefels et al, 2007). Recent studies are now working with incorporation of stable isotope (D 2 O or NaH 13 CO 3 ) into DMSP to measure de novo DMSP synthesis rates (Stefels et al, 2009;Archer et al, 2018), which would be useful in studies aiming at deciphering the physiological roles of DMSP and its derivates.…”
Section: Dmsp and Dmso Might Not Be Part Of The Antioxidant Networkmentioning
confidence: 99%